Alterações morfoanatômicas em plantas de Lithraea molleoides (Vell.) Engl. submetidas ao alagamento - Medri, Moacyr Eurípedes; Ferreira, Ana Cláudia; Kolb, Rosana Marta [UNESP]; Bianchini, Edmilson; Pimenta, José Antonio; Davanso-Fabro, Viviane Maria; Medri, Cristiano (Universidade Estadual de Maringa, 2007)
Flooding effects in Lithraea molleoides plants were studied. Young plants were kept under drained and flooded soil over a period of 35 days. For growth and development analyses, the length and diameter of stem and main root and the dry weight of roots, stem, and leaves were measured. For anatomical studies, sections of fresh and fixed roots, stem bases and leaves were made using standard procedures in vegetal anatomy. The stress reduced the dry weight increment of plants without causing the death of roots or the abscission of leaves. In the stem base, flooding induced the hypertrophy of lenticels and the increase of intercellular space and reduction lower starch contents, in the cortex. Plants flooded displayed greater percentage of cortical intercellular space in the secondary roots and lower investment in secretory structure formation in the stem base. It can be suggested that flooding reduced the recourses allocation to growth. These recourses could be used in morphological alterations, such as hypertrophied lenticels and increase of intercellular spaces, that could contribute to plants survival during stress period, probably, due maintenance of aerobic respiration.
Morpho-anatomical alterations in plants of Lithraea molleoides (Vell.) Engl. submitted to flooding
Keywords: Aerenchyma; Anatomy; Flooding; Lenticel; Lithraea molleoides; Morphology; starch; controlled study; dry weight; intercellular space; lithraea molleoides; morphology; nonhuman; plant; plant leaf; plant root; plant stem; survival; Lithrea molleoides